2013
DOI: 10.3109/02713683.2013.850099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smoking on Choroidal Thickness in Healthy Smokers

Abstract: Smoking caused acute, significant increase in choroidal thickness that returned to baseline levels after 1 h. The choroidal and retinal thicknesses did not differ significantly between the healthy young smokers and non-smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 27 publications
1
53
0
3
Order By: Relevance
“…Bourke et al reported a correlation between untreated systemic hypertension and choroidopathy (29) . The reduction of CT has been reported in a study with smokers, which was thought to be due to increased resistance in the retinal vasculature (30) . Similarly, we observed that the subfoveal, temporal, and nasal CT measurements at 500 µm, 1000 µm, and 1500 µm were significantly lower in migraine patients compared with those in controls (p<0.01).…”
Section: Discussionmentioning
confidence: 72%
“…Bourke et al reported a correlation between untreated systemic hypertension and choroidopathy (29) . The reduction of CT has been reported in a study with smokers, which was thought to be due to increased resistance in the retinal vasculature (30) . Similarly, we observed that the subfoveal, temporal, and nasal CT measurements at 500 µm, 1000 µm, and 1500 µm were significantly lower in migraine patients compared with those in controls (p<0.01).…”
Section: Discussionmentioning
confidence: 72%
“…This information highlights one of the limitations of our study. A recent study reported that smoking caused acute, significant increase in CT that returned to baseline level after 1 h [27]. Another study stated that phosphodiesterase-5 inhibitors increased CT [28].…”
Section: Discussionmentioning
confidence: 96%
“…Ulaş ve ark., sigara içme sonrası akut dö-nemde koroid kalınlığının arttığını fakat bir saat sonra normal değerlerine geri döndüğünü göster-mişlerdir. 33 Bununla birlikte, sigara içen ve içme-yen sağlıklı bireylerde koroid ve retina kalınlığını benzer bulmuşlardır.…”
Section: Discussionunclassified